Techniques for sperm evaluation using fluorescent probes - Cunha, Andrielle Thainar Mendes; Carvalho, José De Oliveira [UNESP]; Dode, Margot Alves Nunes (Universidade Estadual de Londrina, 2015)
A variety of laboratory tests were developed to obtain more reliable results of sperm evaluation and increase the accuracy of sperm fertility predictions. These tests detected damage of sperm specific compartments or organelles, which cannot be detected in routine sperm analysis. The use of fluorescent probes and detection using fluorescent microscopy or flow cytometry is an important tool but a more precise and accurate laboratory test is needed. Propidium iodide and 6-carboxyfluorescein diacetate are used for evaluations of plasmatic membrane integrity. Fluorescein isothiocyanate, associated with conjugated lecithin Psium sativum or Arachis hypogaea, are used for evaluations of acrosome integrity. Two probes, MitoTracker or Rhodamine123, are generally used to measure the absence or presence of mitochondrial potential. However, a better option is 5,5'; 6,6' - tetrachloro - 1,1'; 3,3' - tetraetilbenzimidazolil-carbocyanine (JC-1) dye, which assesses not only the presence of mitochondrial potential and distinguished spermatozoa with poorly and highly functional mitochondria. Two techniques, TUNEL or COMETA, and the Acridine Orange Test (AOT) dye are used to evaluate chromatin integrity. A fluorescence technique based on chlortetracycline (CTC) or Merocyanine 540 is used to estimate whether sperm pass by or through the capacitation process. This review focuses on the fluorescent probes that are most widely used to evaluate plasma membrane integrity, capacitation, acrosome integrity, chromatin integrity and mitochondrial potential.
Keywords: Cryopreservation; Fluorescence microscopy; Sperm